Spc98p directs the yeast γ-tubulin complex into the nucleus and is subject to cell cycle-dependent phosphorylation on the nuclear side of the spindle pole body - Pereira, Gislene; Knop, Michael; Schiebel, Elmar (Molecular biology of the cell, 1998)
In the yeast Saccharomyces cerevisiae, microtubules are organized by the spindle pole body (SPB), which is embedded in the nuclear envelope. Microtubule organization requires the γ-tubulin complex containing the γ-tubulin Tub4p, Spc98p, and Spc97p. The Tub4p complex is associated with cytoplasmic and nuclear substructures of the SPB, which organize the cytoplasmic and nuclear microtubules. Here we present evidence that the Tub4p complex assembles in the cytoplasm and then either binds to the cytoplasmic side of the SPB or is imported into the nucleus followed by binding to the nuclear side of the SPB. Nuclear import of the Tub4p complex is mediated by the essential nuclear localization sequence of Spc98p. Our studies also indicate that Spc98p in the Tub4p complex is phosphorylated at the nuclear, but not at the cytoplasmic, side of the SPB. This phosphorylation is cell cycle dependent and occurs after SPB duplication and nucleation of microtubules by the new SPB and therefore may have a role in mitotic spindle function. In addition, activation of the mitotic checkpoint stimulates Spc98p phosphorylation. The kinase Mps1p, which functions in SPB duplication and mitotic checkpoint control, seems to be involved in Spc98p phosphorylation. Our results also suggest that the nuclear and cytoplasmic Tub4p complexes are regulated differently.
Gesehen am 31.08.2017